Perlindungan Hukum Terhadap Konsumen Atas Penjualan Screw Orthopedi Tanpa Melalui Uji Kelayakan dan Izin Edar (Jurnal Hukum Magnum Opus, 2023)
Medical devices are a promising commodity, where currently medical devices are international trade standards, one of which is Indonesia. The surge and the increasing need for a medical device resulted in business actors who were fraudulent in producing and trading medical device products. Not a few consumers are harmed due to lack of awareness of consumers in buying a product. The absence of supervision carried out by the health supervisory agency in distributing medical devices has resulted in many fraudulent business actors in producing and selling medical device products. Therefore, legal protection efforts are needed for consumers from the health minister who is in charge of overseeing the circulation of medical device products. The aim of this research is to find out and understand the legal protection for consumers on the sale of medical devices without a distribution permit. This study uses the method of normative juridical law by using statutory and conceptual approaches. Implementation of legal protection for consumers from the circulation of medical devices that do not go through a distribution permit, for this reason it is necessary to have an implementation process related to supervision of business actorswho produce and distribute medical devices, in terms of business entity permits, production materials, and product distribution permits. Ideal legal protection for consumers from the circulation of medical devices without going through due diligence and distribution permits, withdirect supervision and inspection, consumers must be careful and careful in buying products, and producers must pay attention to the safety and comfort of consumers and must also use safe raw materials and not dangerous, because business actors are required to guarantee thequality of goods or services produced and traded based on the provisions of the quality standards of goods or services. Keywords: business actor; consumer protection; medical devices Abstrak Alat kesehatan menjadi komoditas yang menjanjikan, di mana saat ini alat kesehatan menjadi standar perdagangan internasional, salahsatunya adalah negara Indonesia. Melonjak dan semakin dibutuhkannya sebuah alat kesehatan, timbul para pelaku usaha yang curang dalammemproduksi dan memperdagangkan produk alat kesehatan. Tidak sedikit para konsumen yang dirugikan akibat kurang kewaspadaan konsumen dalam membeli sebuah produk. Tidak adanya pengawasan yang dilakukan oleh badan pengawas kesehatan dalam mengedarkan alat kesehatan membuat banyaknya pelaku usaha yang curang dalam memproduksi maupun menjual produk alat kesehatan. Oleh karena itudiperlukan upaya perlindungan hukum terhadap konsumen dari menteri kesehatan yang bertugas mengawasi peredaran produk alat kesehatan. Tujuan penelitian untuk mengetahui dan memahami perlindungan hukum terhadap konsumen atas penjualan alat kesehatan tanpaadanya izin edar. Penelitian ini menggunakan metode hukum yuridis normatif dengan menggunakan pendekatan perundang- undangan dankonseptual. Pelaksanaan perlindungan hukum terhadap konsumen dari beredarnya alat kesehatan yang tidak melalui izin edar, untuk itu perlu adanya proses pelaksanaan terkait dengan pengawasan terhadap pelaku usaha yang memproduksi dan mengedarkan alat kesehatan, dari segi izin badan usaha, bahan produksi, dan izin edar produk. Perlindungan hukum yang ideal terhadap konsumen dari beredarnya alat kesehatantanpa melalui uji kelayakan dan izin edar, dengan pengawasan dan pemeriksaan langsung, konsumen harus teliti dan cermat dalam membeli produk, serta produsen harus memperhatikan keamanan dan kenyamanan dari konsumen dan juga harus menggunakan bahan baku yangaman dan tidak berbahaya, karena pelaku usaha wajib menjamin mutu barang atau jasa yang diproduksi dan diperdagangkan berdasarkan ketentuan standar mutu barang atau jasa. Kata kunci: alat kesehatan; perlindungan konsumen; pelaku usaha